ANALISIS PENGARUH FAKTOR METEOROLOGI TERHADAP KONSENTRASI PM10 MENGGUNAKAN REGRESI LINIER BERGANDA(STUDI KASUS: DAERAH DAGO PAKAR DAN CISARANTEN, BANDUNG)ANALYSIS OF THE INFLUENCE OF METEOROLOGICAL FACTORS TO PM10 CONCENTRATION USING - Ana Turyanti (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2011)
Air pollution was influenced by meteorological condition. Atmospheric stability and wind are very important meteorological factors such as solar radiation, temperature, relative humidity, wind and its stability. This study analyzes the influence of meteorological factors to PM10 concentration in Bandung, West Java, as the case study. We used the data from Air Quality System Monitoring (AQMS) at Dago Pakar Stastion as the refference of background area and Cisaranten Wetan as the refference of industrial area. This study used multiple linear regression method to analyze the influence of solar radiation, temperature, relative humidity (RH) and wind velocity to concentration of PM10. The result of this analysis is the meteorological factors that influence PM10 concentration are different for both of location. At Dago, wind velocity is not a significant factor influencing fluctuation of PM10 concentration. However, for Cisaranten Wetan it significantly influences the PM10 concentration with negative correlation. The meteorological factors at Dago that significantly influence PM10 concentration are solar radiation (Rad), temperature (T) and relative humidity (RH), with the equation Yi = -87.334 + 0.023Rad + 3.184T + 0.621RH; while at Cisaranten Wetan, the significant meteorological factors are radiation, relative humidity and wind velocity (V), with equation Yi = 16.0842 + 0.028Rad + 0.504RH - 9.184V. Wind velocity at Cisaranten Wetan had a larger range than that of Dago. This wind has a velocity of 5 m/sec which potentially transports particulates to other areas that can decrease PM10 concentration.